A more elite soldier : pursuing a life of purpose - Holton, Chuck ([S.l.] : Multnomah Books, 2003)
The rigor of becoming an Airborne Ranger is exceeded only by the challenge of being one - but those who join their ranks find fulfillment in something bigger than themselves. In the same way, pursuing God's objectives energizes our everyday lives. Former U.S. Army Ranger Chuck Holton shows how God oversees our training and gives each of us specific skills to accomplish the mission He has for us in this great spiritual war. Riveting action and powerful vignettes offer potent spiritual ammunition for the battles of every Christian serving in God's army. Find out what it takes to be a more elite soldier.
Keywords: Armed Forces--Commando troops; Christian biography; Religion; Soldiers; United States